Pengaruh Model Pembelajaran Problem Based Learning Pada Mata Pelajaran Otomatisasi Tata Kelola Humas dan Keprotokolan Terhadap Hasil Belajar dan Kemampuan Berpikir Kritis Siswa Kelas XI OTKP SMK Ketintang Surabaya - Annisa Ikhlasul Amaliyah; Brillian Rosy (Universitas Negeri Surabaya, 2020)
This study aims to determine the effect of the problem based learning model of learning in Public Relations and Protocol on learning outcomes and critical thinking skills of class XI OTKP students at SMK Ketintang Surabaya. This type of experimental research uses a quasi experimental design with a non-equivalent control group design. Data analysis used normality test, homogeneity test, t-test and gain score. T test results based on the value of student learning outcomes indicate the value of tcount> ttable (2.898>2.005) and the results of t-test based on the value of students' critical thinking skills. Show the value of tcount>ttable (10,554> 2,005). Then the difference (gain score) pre-test and post-test values obtained that tcount> ttable (4.643>2.005). With the difference (gain score) the average value of the pre-test and post-test experimental class 18.036 is greater than the pre-test value of the control class of 10.536. So it can be concluded that there is an influence of problem based learning model of learning on the subject of automation in Public Relations and Protocol management on learning outcomes and critical thinking skills of students in class XI OTKP SMK Ketintang Surabaya.